2019
DOI: 10.1016/j.anr.2019.11.003
|View full text |Cite
|
Sign up to set email alerts
|

How Strong is the Evidence for the Anxiolytic Efficacy of Lavender?: Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: Purpose: Although lavender is purported to possess anxiolytic and sedative properties and is often recommended for relieving anxiety, the efficacy of lavender has not been well established. Thus, this review aimed to evaluate the anxiolytic effects of lavender aromatherapy. Methods: Ten data bases were searched for studies published between 2000 and 2018. Randomized controlled trials investigating the anxiolytic effects of lavender aromatherapy with any type of application for persons with or without clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 36 publications
6
40
0
19
Order By: Relevance
“…Of particular interest are the effects of terpenes and terpenoids on the suppression of inflammatory and infection responses and the immunomodulatory properties of these compounds (117). Aromatherapy has been explicitly and/or implicitly part of CIM worldwide, particularly in the field of botanical medicine, where such properties are used to achieve specific therapeutic goals (118)(119)(120), for example to reduce anxiety (121). Due to their anti-microbial portfolio, several of these substances are of interest for the prevention of (respiratory) infections, the supportive treatment of conventional treatments, or a stand-alone CIM therapy in the case of a mild course of respiratory tract infections (122).…”
Section: Aromatherapymentioning
confidence: 99%
“…Of particular interest are the effects of terpenes and terpenoids on the suppression of inflammatory and infection responses and the immunomodulatory properties of these compounds (117). Aromatherapy has been explicitly and/or implicitly part of CIM worldwide, particularly in the field of botanical medicine, where such properties are used to achieve specific therapeutic goals (118)(119)(120), for example to reduce anxiety (121). Due to their anti-microbial portfolio, several of these substances are of interest for the prevention of (respiratory) infections, the supportive treatment of conventional treatments, or a stand-alone CIM therapy in the case of a mild course of respiratory tract infections (122).…”
Section: Aromatherapymentioning
confidence: 99%
“…The microprogation of L. viridis was performed and in vitro shoot cultures and microprogated plants have also been a target of study [46,64]. In shoot cultures, authors [64] reported that 1,8-cineole (7) and α-pinene (8) were the most important compounds. Camphor (6) was the third most important volatile compound in the in vitro shoots EOs.…”
Section: Lavandula Pedunculata (Miller)mentioning
confidence: 99%
“…When antioxidant and anti-protozoal activities of L. viridis EOs were compared to those of L. luisieri, it was verified that they were less active (Table 1). When different extraction methods were used for obtaining the volatile fractions and EOs, Costa et al [47] verified that hydrodistillation was the best method for obtaining samples with higher antioxidant and anti-acetylcholinesterase activities than the volatile samples obtained by supercritical fluid extraction (7). In vitro anti-fungal activities of L. stoechas subsp.…”
Section: Lavandula Pedunculata (Miller)mentioning
confidence: 99%
See 1 more Smart Citation
“…Lavender has become an increasingly popular alternative due to increased knowledge of its pharmacological effects and significant clinical potential on its own or as adjuvant therapy in different disorders (Koulivand, Khaleghi Ghadiri, & Gorji, 2013). However, due to issues, such as methodological inadequacies, small sample sizes, short duration of lavender application, lack of information regarding dose rationale, variation between efficacy and effectiveness trials, the variability of administration methods, the absence of a placebo comparator, and lack of control groups, more standard experiments and research are needed to confirm the beneficial effect of lavender with neurological disorders (Kang, Nam, Lee, & Kim, 2019;Koulivand et al, 2013). Some research did not define the contents of lavender and several factors, such as temperature, skin type and quality, and the size of area being treated, which may affect the level and rate of lavender absorption after massage or aromatherapy, were not considered (Kang et al, 2019;Koulivand et al, 2013).…”
Section: Lavender Oil Diffusormentioning
confidence: 99%